Surgical uprighting of impacted mandibular second molar: a narrative review - Sangha Tarnjit Kaur; Sangha Sukhneet Kaur; Hanna Brandon; Tayab Tabassum; Padala Soumya (EDP Sciences, 2021)
Early diagnosis of impacted mandibular second molar (MM2) is critical since treatment at a later stage can be complicated. It often requires a multidisciplinary approach. Surgical uprighting of impacted MM2 appears to be a safe, effective, and a reliable alternative to conventional orthodontic mechanics with minimal risk of morbidity or pulpo-periodontal problems. Timely diagnosis is critical and factors affecting treatment outcomes must be assessed for a successful outcome. Although surgical uprighting or repositioning is the most commonly prescribed option for MM2 management, there isn't a review of literature that discusses the etiology, assessment, and surgical management of impacted MM2 with an emphasis on surgical uprighting technique and comparing various factors that affect the outcome.